2008
DOI: 10.1508/cytologia.73.91
|View full text |Cite
|
Sign up to set email alerts
|

Morphological and Genetic Variation in the Cosmopolitan Snow Alga Chloromonas nivalis (Volvocales, Chlorophyta) from Japanese Mountainous Area

Abstract: Summary Mature zygotes of the cosmopolitan snow alga Chloromonas nivalis (Chodat) Hoham & Mullet [ϭScotiella nivalis (Chodat) Fritsch] collected from Mt. Gassan, Yamagata Prefecture, were examined by scanning electron microscopy (SEM) and single-cell sequencing of the large subunit of Rubisco (rbcL) genes. The present SEM demonstrated that Japanese samples have at least two types of flanges on the zygote wall (straight and sigmate). Although these types fell within the morphological variability of C. nivalis a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 17 publications
2
23
0
Order By: Relevance
“…nivalis, which are commonly reported from snowfields in Japan, as well as worldwide (Muramoto et al, 2008). The shape, size, and pigmentation of the type A algal cells corresponded with those of the cysts of Cr.…”
Section: Life Cycle Of Snow Algae In Tohkamachimentioning
confidence: 60%
See 2 more Smart Citations
“…nivalis, which are commonly reported from snowfields in Japan, as well as worldwide (Muramoto et al, 2008). The shape, size, and pigmentation of the type A algal cells corresponded with those of the cysts of Cr.…”
Section: Life Cycle Of Snow Algae In Tohkamachimentioning
confidence: 60%
“…Two morphological types of snow algae were observed in the site, and they are likely to be Cr. nivalis, which is a common species on seasonal snow surfaces in Japan, as well as worldwide (Muramoto et al, 2008). The timing of the algal appearance on the snow surface varied from February 4 to February 25 in the four winters.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…nivalis strain UTEX SNO71 and field-collected C . nivalis zygote specimens examined in previous studies [ 19 , 20 , 41 ] was performed by single-gene phylogenetic analyses using 18S rDNA and rbc L sequences ( S4 and S5 Figs). Both trees reconstructed the monophyletic groups B–D which were robustly resolved in the multigene phylogenetic tree ( Fig 4 ), but statistical support values for monophyly were lower.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, we set three partitions (first, second, and third codon positions) for BI and ML analysis of rbc L gene sequences according to a previous study [ 4 ]. Additional operational taxonomic units were selected from previous studies [ 19 , 20 , 41 ] and shown in S3 Table .…”
Section: Methodsmentioning
confidence: 99%